Learning Community: Kanchanaburi Organic Agriculture Community Enterprise Network - Udomwech, Aphinya (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2022)
The research objectives were to study the knowledge and network management, analyze the human resource development mechanism, and to synthesize a model of learning community development for the Kanchanaburi Organic Agriculture Community Enterprise Network. The 92 key informants were selected using purposive sampling methods consisting of farmers in the Kanchanaburi Organic Community Enterprise Network, and representatives of development partners. Data were collected through in-depth interviews, small group discussions, and observations. Data were analyzed based on content analysis and interpretation. Data verification used a triangulation technique, while information accuracy was tested by verifying it with informant representatives. The results revealed that the learning community development to the Kanchanaburi Organic Agriculture Community Enterprise Network had basic principles consisting of: sufficiency, self-reliance, and organic agriculture. Practical intellectual learning based on social capital and participation created a body of knowledge consisting of: sufficiency economy philosophy, lifelong learning, wisdom and dependence on natural resources, production and standards, situation analysis, group management, digital communication and network-based marketing management, and the integration of public power. Learning network management identified the components: learning, participatory network management, and partner synergy. Human development mechanisms consisted of concepts and practices, development policies and strategies, networks, and change agents. Synthesizing these elements resulted in the network's learning community development model being fundamentally at the heart of the process. Development mechanisms stimulated and reinforced the learning process by using knowledge and network management to contribute to the development of the network's potential to be self-managed on the basis of sustainable development.